Neutrophil-to-Lymphocyte Ratio Is Independently Associated With Severe Psychopathology in Schizophrenia and Is Changed by Antipsychotic Administration: A Large-Scale Cross-Sectional Retrospective Study - Zhou, Xia; Wang, Xiaolan; Li, Rui; Yan, Jun; Xiao, Ying; Li, Weiguang; Shen, Hong (Frontiers in Psychiatry, 2020)
Background: Immunological and inflammatory mechanisms play an important role in schizophrenia. The neutrophil-to-lymphocyte ratio (NLR) is a value obtained by dividing the absolute number of neutrophils by the absolute lymphocyte count and represents a biomarker of systemic inflammatory response. There are studies investigating NLR association with psychopathology. However, the relationship has been only studied in small numbers of patients with schizophrenia, which leads to conflicting results and makes the meta-analytic data difficult to interpret. The aim of this study is to perform large-scale cross-sectional analysis on the potential correlation between NLR and disease severity in schizophrenic patients with or without medication. Methods: This cross-sectional retrospective study was conducted in Nanjing Medical University Affiliated Brain Hospital. We identified inpatients with schizophrenia between July 12, 2018 and March 27, 2019 and collected data of NLR, the Clinical Global Impression Severity scale (CGI-S) score and the Brief Psychiatric Rating Scale (BPRS) score. Results: The records of 1144 identified patients (10.8% drug-free patients) were analyzed. We found that NLR was significantly decreased in schizophrenic patients after antipsychotic administration and there was the discrepant correlation between NLR and psychiatric symptoms in patients with or without antipsychotic medication. The results of multivariate logistic regressions showed that NLR was positively associated with the severity of disease (i.e. the CGI-S score and the BPRS total score) in drug-free patients, and it was negatively associated with the BPRS negative symptoms (i.e. the BPRS negative symptoms score) in drug-therapy patients. Conclusion: The study is the first to confirm the hypothesis that NLR is independently associated with severe psychopathology in schizophrenia and is changed by antipsychotic administration.